2020
DOI: 10.1055/a-1327-5939
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of laparoscopic and endoscopic cooperative surgery for duodenal neoplasm: a retrospective multicenter study

Abstract: Background and study aims A delayed perforation can often occur after endoscopic treatment for duodenal neoplasms and cause fatality due to leakage of pancreatic and bile juices. We aimed to evaluate the feasibility and safety of laparoscopic and endoscopic cooperative surgery for duodenal neoplasms (D-LECS) in a multicenter retrospective study. Patients and methods The clinical characteristics and surgical outcomes of 206 patients with duodenal neoplasms in whom D-LECS had initially been attempted at one of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Most patients (74.4 %) were followed up without treatment, and the remaining 25.6 % of patients underwent treatment such as ER or surgical resection (SR) after being followed up for ≥ 6 months. There were 8 lesions (6.4 %) that required SR, all of which were local resection including laparoscopic and endoscopic cooperative surgery (LECS) 22 . The reasons for SR were large size (> 20 mm) in four lesions and poor endoscopic maneuverability in four lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Most patients (74.4 %) were followed up without treatment, and the remaining 25.6 % of patients underwent treatment such as ER or surgical resection (SR) after being followed up for ≥ 6 months. There were 8 lesions (6.4 %) that required SR, all of which were local resection including laparoscopic and endoscopic cooperative surgery (LECS) 22 . The reasons for SR were large size (> 20 mm) in four lesions and poor endoscopic maneuverability in four lesions.…”
Section: Resultsmentioning
confidence: 99%
“…This technique is believed to compensate for the high perforation rate in ESD with reinforcement using seromuscular sutures at the mucosal defect site. Nunobe et al [ 29 ] showed that the rates of en bloc and R0 resection during D-LECS were 96% (198/206) and 95% (196/206), respectively. In this study, D-LECS had the same indications as ESD in duodenal tumors, for example, adenoma and mucosal adenocarcinoma without around the ampulla of Vater.…”
Section: Treatments For Snadetsmentioning
confidence: 99%
“…Another way to prevent delayed AE is suturing the wound from the peritoneal side by laparoscopy assistance in addition to flexible endoscopy from inside the duodenum lumen. This novel surgical procedure, named endoscopic cooperative surgery (D-LECS), was first reported in 2015 [42] . A retrospective case series with 206 cases undergoing D-LECS revealed 95% R0 resection rate, 1.5% perforation rate, and 1% bleeding rate, suggesting favorable outcomes [43] .…”
Section: Suturingmentioning
confidence: 99%